2023
DOI: 10.3390/jfb14100486
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Biofilm Formation on Zirconia Implant Surfaces Treated with Femtosecond and Nanosecond Lasers

Soo Kyum Bihn,
Keunbada Son,
Young-Tak Son
et al.

Abstract: (1) Background: The purpose of this study was to evaluate how a zirconia implant surface treated with laser technology affects the degree of biofilm formation. (2) Methods: Experimental titanium (Ti) disks were produced that were sandblasted with large grit and acid-etched (T), and they were compared with zirconia (ZrO2) discs with a machined (M) surface topography; a hydrophilic surface topography with a femtosecond laser (HF); and a hydrophobic surface topography with a nanosecond laser (HN) (N = 12 per surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A surface sandblasted with large-grit sand and acid-etched (SLA) is adopted to induce surface erosion on blasted surfaces [29]. This method combines large-grit sand particles with acid etching to achieve macro-roughness and micro-pits [30], seeking enhanced surface roughness and osseointegration [31][32][33][34]. Cho and Jung [31] identified that SLA surfaces house expansive cavities (diameter of 5-20 µm) and micro-pits (diameter of 0.5-3 µm), leading to augmented surface roughness and area.…”
Section: Introductionmentioning
confidence: 99%
“…A surface sandblasted with large-grit sand and acid-etched (SLA) is adopted to induce surface erosion on blasted surfaces [29]. This method combines large-grit sand particles with acid etching to achieve macro-roughness and micro-pits [30], seeking enhanced surface roughness and osseointegration [31][32][33][34]. Cho and Jung [31] identified that SLA surfaces house expansive cavities (diameter of 5-20 µm) and micro-pits (diameter of 0.5-3 µm), leading to augmented surface roughness and area.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the results of in vitro studies assessing the distortion generated by intraoral scanning systems for oral rehabilitation with more than three implants were systematically reviewed, showing that digital impression systems generate significant errors during scanning in extensive implant restorative treatments. This is influenced by scanning technology, inter-implant distance, and scanning body type [7][8][9][10].…”
mentioning
confidence: 99%